1977
DOI: 10.1007/bf00582206
|View full text |Cite
|
Sign up to set email alerts
|

Activation of afferent cardiac sympathetic nerve fibers of the cat by pain producing substances and by noxious heat

Abstract: Afferent discharges of 64 single units were recorded from the left cardiac sympathetic nerve of anesthetized cats. Mechano-sensitive terminals of the afferent fibers were localized in the extrapulmonary part of the pulmonary artery, left atrium, left ventricle and left pericardium, as determined by direct mechanical probing of the heart after death of the animals. Conduction velocity of the fibers ranged from 2.5 to 14.6 m/s. Excitation of these Adelta-fibers with mechanically excitable endings was produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
3

Year Published

1980
1980
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 18 publications
1
30
3
Order By: Relevance
“…Thus, Uchida & Murao (1974a) reported that the ventricular nerve endings excited by bradykinin fired in time with the cardiac cycle, and they postulated that bradykinin sensitized these mechanosensitive endings to their normal stimulus, which was provided by the rhythmical mechanical changes in the ventricular wall. Nishi, Sakanashi & Takenaka (1977) confirmed that bradykinin increased the firing of mechanosensitive endings in the ventricle; they also showed that the endings were supplied by myelinated fibres. These latter investigators, however, used very high concentrations of bradykinin, which appeared to evoke only modest responses.…”
Section: Introductionmentioning
confidence: 60%
“…Thus, Uchida & Murao (1974a) reported that the ventricular nerve endings excited by bradykinin fired in time with the cardiac cycle, and they postulated that bradykinin sensitized these mechanosensitive endings to their normal stimulus, which was provided by the rhythmical mechanical changes in the ventricular wall. Nishi, Sakanashi & Takenaka (1977) confirmed that bradykinin increased the firing of mechanosensitive endings in the ventricle; they also showed that the endings were supplied by myelinated fibres. These latter investigators, however, used very high concentrations of bradykinin, which appeared to evoke only modest responses.…”
Section: Introductionmentioning
confidence: 60%
“…Previous electrophysiological studies conducted in visceral tissues, including testis (Koda et al, 1996), heart (Nishi et al, 1977), and airways (Matsumoto et al, 1992(Matsumoto et al, , 1993Riccio et al, 1996), have shown that histamine can excite polymodal nociceptors having both A␦ unit and C-unit CVs, probably through activation of the H1 receptor. The results of our studies, however, suggest that histamine excites mainly Cunit meningeal nociceptors.…”
Section: Discussionmentioning
confidence: 98%
“…Myocardial ischemia and hypoxia are associated with pain (SUTTON and LUETH, 1930;BURCH and DEPASQUALE, 1962;GUZMAN et al, 1962) and are accompanied by accumulation of lactic acid (UCHIDA and MURAO, 1975), bradykinin and prostaglandins (KIMURA et al, 1973;UCHIDA and MURAO, 1974d;STASZEWSKA-BARCZAK et al, 1976;NISHI et al, 1977;BAKER et al, 1980;LOMBARDI et al'., 1981;KOLEY et al, 1985). Earlier it had been suggested by LINDGREN and OLIVECRONA (1947) as well as WHITE and BLARD (1948) that sympathetic afferents participate in transmitting impulses leading to cardiac pain in man.…”
Section: Discussionmentioning
confidence: 99%